Social values of angling tourism in the Garo Hills of Meghalaya, North East India: fish farmers’ perspectives - Sangma, Annastaycya Simsang; Lahiri, Biswajit; Ghosh, Amitava; Pal, Prasenjit; Singh, Soibam Khogen; Tengli, Mahesh Bhimashankar; Meinam, Martina; Chandegara, Abhay Kumar (Journal of Fisheries, 2025)
Angling tourism is gaining popularity and offers an alternative livelihood opportunity for the fish farmers of the Garo Hills region of Meghalaya, India. This research aims to provide insights into the social value of angling tourism among the fish farmers involved in angling tourism in the area and to identify its determinants. A sample of one hundred fish farmers was selected using snowball sampling from five districts of the Garo Hills, and data were collected using a semi-structured interview schedule. Most farmers considered fisheries a secondary occupation and were sceptical of angling tourism. The multiple stepwise regression analyses revealed that entry fees for daily angling besides competition and secondary occupation negatively impacted social value scores. In contrast, the educational status of fish farmers, annual investment in angling tourism, fish farming experience, total registered anglers annually, and family type positively impacted social value scores. The study confirmed that angling tourism fosters sustainable development within rural communities by nurturing social values and augmenting biodiversity conservation, and economic benefits. Overall, the study provides valuable information on the scope and prospects of angling tourism in leveraging social values and its potential to uplift rural people’s social and financial status.